Congenital choroidal melanocytoma in a child with ocular melanocytosis. Issue 10 (30th October 2019) - Maniar, Arpita; Jakati, Saumya; Kaliki, Swathi
Abstract : A 1-day-old child was brought to the clinic for evaluation of enlarged right eye (OD). On examination, OD showed buphthalmos with diffuse scleral melanocytosis, fleshy blackish-brown extrascleral mass with corneal extension, and secondary glaucoma. Anterior segment evaluation revealed darkly pigmented iris and fundus evaluation OD revealed a darkly pigmented choroidal lesion. The left eye was within normal limits. A clinical diagnosis of choroidal melanocytoma with ocular melanocytosis was made. Enucleation OD followed by orbital implant was performed. Histopathology showed features of diffuse ocular melanocytosis involving limbus, iris, ciliary body, choroid, sclera, optic nerve head, optic nerve sheath, along with choroidal melanocytoma with extrascleral tumour extension. We presume that choroidal melanocytoma may have arisen from ocular melanocytosis.